Malaria Surveillance in the Anak Dalam Tribe, Jambi, Indonesia (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
Transmission of malaria is common in countries with tropical and subtropical. In several cases, malaria presents in the sufferer especially in individuals that have never received treatment shortly. As the early phase of patient identification, screening is important as an effort to eradicate malaria, in addition to the gold standard which currently used, other diagnostic tools are needed to conduct a malaria incidence survey to obtain comparative data using 3 diagnostic tools, goal standard checks, which are currently unable to detect asymptomatic malaria. This study aims to compare three standard diagnostic test (Rapid Diagnostic Test, Giemsa, and Nested Polymerase Chain Reaction) for the measurement of malaria prevalence within the Anak Dalam Tribe community in Jambi, Indonesia. This descriptive research with a survey design was conducted on 99 persons in Anak Dalam Tribe. It was discovered that majority of the respondents were the adult age category (52.5%),were female (50.5%). The prevalence of this infectious disease as detected by Rapid Diagnostic Test, microscopy, and Nested Polymeras Chain Reaction examination were 3%, 5% and 35.3% respectively. Non-Plasmodium falciparum was detected by examining samples with Rapid Diagnostic Test, on microscope, P. vivax and P. falciparum were found, while on Nested Polymerase Chain Reaction, two bands at 120bp and 205bp showed P. vivax and P. falciparum respectively. Nested Polymeras Chain Reaction is more sensitive to detected asymptomatic malaria, however, Rapid Diagnostic Test and Giemsa sensitive with parasitemia threshold.